The role of male visual and chemical cues on the activation of female courtship behaviour in the sex-role reversed blenny, Salaria pavo - Barata, Eduardo N. (2008)
Chemical cues during courtship in peacock blenny Salaria pavo did not add significantly to the response of visual stimuli and females did not court when a male was not visible. The results showed that female S. pavo courtship behaviour was elicited exclusively by male visual features and not by a multicomponent signal in different sensory modalities. The time spent by females courting the male and exhibiting the nuptial colouration during visual trials correlated with the size of the male's crest, suggesting a signalling function for this trait. Alternative hypothesis for the function of the putative pheromones released by the male's anal gland are discussed. Evidence that female sexual motivation decreases towards the end of the breeding season is also provided, which should be considered in future mate choice experiment